Genetic diversity and population structure within Botswana: association with HIV-1 infection - Thami, Prisca Kerapetse (Department of Clinical Laboratory Sciences, 2021)
Southern Africa is disproportionately affected by HIV-1, with Botswana being among the most affected countries. The interindividual heterogeneity in susceptibility or resistance to HIV-1 and progression upon infection is attributable to, among other factors, host genetic variation. Characterisation of human genetic variations can contribute towards understanding the genetic aetiology of HIV-1 and foster development of novel preventive and treatment strategies against HIV-1. Despite the high burden of HIV-1 in Botswana, the population of Botswana is significantly underrepresentation in genomics studies of HIV-1. Furthermore, the bulk of previous genomics studies evaluated common human genetic variations, however, there is increasing evidence of the influence of rare variants in the outcome of diseases which may be uncovered by comprehensive complete and deep genome sequencing. This research aimed to characterise human genomic variations of Batswana in order to elucidate mutation burden, assess population structure and evaluate the role of these genomic variations in susceptibility to HIV-1 and progression through bioinformatics analyses. Whole genome sequences (WGS) of 265 HIV-1 positive and 125 were HIV-1 negative unrelated individuals from Botswana were computationally analysed. The sequences were mapped to the human reference genome GRCh38. Population joint variant calling was performed using Genome Analysis Tool Kit (GATK) and BCFTools. Variant characterisation was achieved by annotating the variants with a suite of databases in ANNOVAR. The genomic architecture of Botswana was assessed through principal component analysis and structure analysis and FST. Cumulative effects of rare variant sets on susceptibility to HIV-1 and progression (CD4+ T-cell decline) were determined with optimized Sequence Kernel Association Test (SKAT-O). Functional analysis of the prioritized variants was performed through gene-set enrichment using databases in GeneMANIA and Enrichr. Variant characterization revealed 24 damaging variants with the most damaging variants being ACTRT2 rs3795263, HOXD12 rs200302685, ABCB5 rs111647033, ATP8B4 rs77004004 and ABCC12 rs113496237. There was admixture of Khoe-San, Niger-Congo and European ancestries observed in the population of Botswana, however, there was no evidence of overall substructure among the HIV-1 positive/negative individuals of Botswana, indicating similar genetic exposure among HIV-1 samples. No variant set was significantly associated with susceptibility to HIV-1, while sets of novel rare-variants within the ANKRD39 (8.48 x 10- 8 ), LOC105378523 (7.45 x 10-7 ) and GTF3C3 (1.36 x 10-6 ) genes were significantly associated with HIV-1 progression. Functional analysis revealed that the variants affected several pathways including chemokine signalling, glycolysis, glycosylation, HIV-1 and host receptor glycoprotein biosynthesis, intracellular transport of molecules and transcription pathways. These findings highlight the significance of whole genome sequencing in pinpointing rare variants of clinical relevance. This PhD thesis unravelled novel genes and novel rare variants that are putatively linked to HIV-1 progression. The thesis contributes towards a deeper understanding of the host genetics HIV-1 and offers promise of population specific interventions against HIV-1.